Use of Cerclage in Triplet Pregnancies With an Asymptomatic Short Cervix. (1st February 2014) - Young, Christopher M.; Stanisic, Tatiana; Wynn, Lisa Blair; Shrivastava, Vineet L.; Haydon, Michael L.; Wing, Deborah A.
Abstract : Objectives: The purpose of this study was to compare the outcomes of triplet pregnancies in women with asymptomatic cervical shortening with and without a cervical cerclage. Methods: A retrospective review of all triplet pregnancies with biweekly serial cervical length surveillance was performed. Cervical shortening was defined as a cervical length of 2.5 cm or less before 24 weeks' gestation. Patients with cervical shortening managed with cerclage were compared to those managed expectantly. The primary outcome was the gestational age at delivery, with secondary outcomes including birth weight, neonatal intensive care unit length of stay, and composite neonatal outcome. Statistical significance was defined as P < .05. Results: Sixteen patients underwent cerclage placement versus 8 managed expectantly (control group). The median gestational ages at delivery were similar between the groups (cerclage, 31.3 weeks; interquartile range [IQR], 29.3–32.3 weeks; control, 29.8 weeks; IQR, 27.5–32.4 weeks; P = .71). The median birth weights were also similar between the groups (cerclage, 1283 g; IQR, 800–1626 g; control, 1109 g; IQR, 776–1500 g; P = .54). There was no significant difference in composite neonatal outcomes between the cerclage and control groups ( P = .67). Conclusions: In this limited case‐control study, we found no benefit in terms of pregnancy prolongation or neonatal outcomes with cerclage placement for triplet gestations complicated by an asymptomatic short cervix.